Human contribution to the record-breaking June and July 2019 heatwaves in Western Europe. (28th August 2020) - Vautard, Robert; van Aalst, Maarten; Boucher, Olivier; Drouin, Agathe; Haustein, Karsten; Kreienkamp, Frank; van Oldenborgh, Geert Jan; Otto, Friederike E L; Ribes, Aurélien; Robin, Yoann; Schneider, Michel; Soubeyroux, Jean-Michel; et al.
Abstract: Two extreme heatwaves hit Western Europe in the summer of 2019, with historical records broken by more than a degree in many locations, and significant societal impacts, including excess mortality of several thousand people. The extent to which human influence has played a role in the occurrence of these events has been of large interest to scientists, media and decision makers. However, the outstanding nature of these events poses challenges for physical and statistical modeling. Using an unprecedented number of climate model ensembles and statistical extreme value modeling, we demonstrate that these short and intense events would have had extremely small odds in the absence of human-induced climate change, and equivalently frequent events would have been 1.5 °C to 3 °C colder. For instance, in France and in The Netherlands, the July 3-day heatwave has a 50–150-year return period in the current climate and a return period of more than 1000 years without human forcing. The increase in the intensities is larger than the global warming by a factor 2 to 3. Finally, we note that the observed trends are much larger than those in current climate models.